2023
DOI: 10.1007/s43032-023-01381-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trophectoderm mRNAs and MicroRNAs with Chromosomal Aneuploidy of Embryo

Masoumeh Esmaeilivand,
Aliyeh Ghasemzadeh,
Behrooz Niknafs
et al.

Abstract: MicroRNAs (miRNAs) and mRNAs can serve as indicators of the chromosomal state of an embryo, with different pro les observed in euploid and aneuploid blastocysts. Examining the levels of miRNAs associated with aneuploidy and euploidy, as well as mRNAs related to implantation, can aid in predicting blastocyst chromosomal normality and improving assisted reproductive technology (ART) outcomes.This study analyzed chromosomal abnromality of 25 blastocysts using uorescence in situ hybridization (FISH) and also the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Assessing blastocoel samples obtained from euploid and aneuploid blastocysts, the results revealed a significant increase of only miR-20a and miR-661 in the blastocoel fluid obtained from aneuploid embryos. Furthermore, the investigation extended to the examination of the selected miRNAs within the biopsied trophectoderm cells of the same blastocysts ( 18 ). The findings showed a significant downregulation of hsa-miR-30c and hsa-miR-372 levels in the aneuploid samples compared to the euploid blastocysts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing blastocoel samples obtained from euploid and aneuploid blastocysts, the results revealed a significant increase of only miR-20a and miR-661 in the blastocoel fluid obtained from aneuploid embryos. Furthermore, the investigation extended to the examination of the selected miRNAs within the biopsied trophectoderm cells of the same blastocysts ( 18 ). The findings showed a significant downregulation of hsa-miR-30c and hsa-miR-372 levels in the aneuploid samples compared to the euploid blastocysts.…”
Section: Resultsmentioning
confidence: 99%
“…The role of miRNA in early development has been previously investigated, showing significant contribution in the process of implantation and stem cell differentiation ( 8 10 ). However, only limited studies have explored the potential of miRNAs in assessing developmental competence of early embryos, and the possible relationship between aneuploidy and miRNA expression ( 11 18 ). In this systematic review, our aim is to identify and combine the reported information on miRNAs with potential association to aneuploidy in preimplantation blastocysts.…”
Section: Introductionmentioning
confidence: 99%